Evaluating signaling bias for synthetic cannabinoid receptor agonists at the cannabinoid CB2 receptor - Monica Patel; Natasha L. Grimsey; Samuel D. Banister; David B. Finlay; Michelle Glass (Pharmacology Research & Perspectives, 2023)
Abstract The rapid structural evolution and emergence of novel synthetic cannabinoid receptor agonists (SCRAs) in the recreational market remains a key public health concern. Despite representing one of the largest classes of new psychoactive substances, pharmacological data on new SCRAs is limited, particularly at the cannabinoid CB2 receptor (CB2). Hence, the current study aimed to characterize the molecular pharmacology of a structurally diverse panel of SCRAs at CB2, including 4‐cyano MPP‐BUT7AICA, 4F‐MDMB‐BUTINACA, AMB‐FUBINACA, JWH‐018, MDMB‐4en‐PINACA, and XLR‐11. The activity of SCRAs was assessed in a battery of in vitro assays in CB2‐expressing HEK 293 cells: G protein activation (Gαi3 and GαoB), phosphorylation of ERK1/2, and β‐arrestin 1/2 translocation. The activity profiles of the ligands were further evaluated using the operational analysis to identify ligand bias. All SCRAs activated the CB2 signaling pathways in a concentration‐dependent manner, although with varying potencies and efficacies. Despite the detection of numerous instances of statistically significant bias, compound activities generally appeared only subtly distinct in comparison with the reference ligand, CP55940. In contrast, the phytocannabinoid THC exhibited an activity profile distinct from the SCRAs; most notably in the translocation of β‐arrestins. These findings demonstrate that CB2 is able to accommodate a structurally diverse array of SCRAs to generate canonical agonist activity. Further research is required to elucidate whether the activation of CB2 contributes to the toxicity of these compounds.